- EVALUASI DAMPAK KINERJA KEUANGAN PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI DENGAN KESETARAAN GENDER SEBAGAI VARIABEL MEDIASI: - - Salsabella Thalia, Novia Andira; Rochmatullah, Mahameru Rossy (JURNAL EKBIS, 2023)
This study aims to find empirical evidence whether economic growth in districts/cities in Indonesia during 2018-2020 is influenced by financial performance in the form of independence ratios, compatibility ratios, effectiveness ratios, efficiency ratios, and growth ratios. This is because economic growth is very important and needed to open opportunities for regions to reduce the number of unemployed and reduce the number of poor people. The population used in this research is all regencies and cities in Indonesia in 2018-2020. The sample selection was carried out using a purposive sampling method, with a final sample size of 146 samples from 46 districts/cities in Indonesia during the 2018-2020 research period. This study uses a multiple linear regression testing model that is tested with the help of SmartPLS. This research concludes that there is an influence between gender equality and economic growth, the ratio of independence and gender equality, and the ratio of harmony to gender equality. Meanwhile, from this study it can also be concluded that there is no influence between efficiency ratios on gender equality, efficiency ratios on economic growth, and independence ratios on economic growth.